Outcome in excised thymomas: role of prognostic factors and impact of additional malignancies on survival. Issue 1 (February 2014) - Granato, F; Blackhall, V; Alessandra, R; Spina, D; Luca, V; Piero, P; Mohiyaddin, S; Asif, M; Kirk, A JB; Giuseppe, Gotti
Background and aims: Although the management of thymomas has been extensively evaluated, the value of prognostic factors in the outcome of these patients remains unclear. Methods and results: The medical records of all patients who underwent resection of thymoma between January 1985 and September 2010 at a single thoracic unit were reviewed. Patients were followed up with reference to disease recurrence and development of additional malignancies (AM). Total thymectomy was performed in all 68 cases. Mean follow-up time was four years. Mean survival was 63.9 months. Mean disease-free interval was 13 months. Factors affecting prognosis were Masaoka staging and WHO histological sub-type. Patients with thymomas had a higher risk of developing AM when compared with a control population of individuals with other tumours ( p  = 0.0002). Among thymomas, the cortical subtype was associated with a higher risk of AM ( p  = 0.047) and mortality ( p  = 0.001). Conclusions: This data confirms that Masaoka staging and WHO histologic sub-type are the most important prognostic factors in patients with thymoma. Moreover, thymomas predominantly arising from the thymic cortex are associated with a higher risk of developing other malignancies and with poorer survival. The cortical origin of thymoma could therefore be considered as a significant prognostic factor.